Utilizing Library Science to Bridge the Gap between Food and Nutritional Sciences and Public Health. (International Journal of Food and Nutritional Sciences, 2022)
This research paper explores the potential of utilizing library science principles to bridge the gap between food and nutritional sciences and public health. The paper highlights the importance of food and nutrition for public health and identifies current challenges and gaps in the field. It then examines the role of library science in addressing these challenges and fostering collaboration between these disciplines. The paper discusses information needs in food and nutritional sciences and how library science can contribute to efficient information organization and retrieval. Additionally, it explores the significance of information literacy and training programs in equipping researchers and practitioners with the necessary skills to access and evaluate relevant information. Through case studies and best practices, the paper provides examples of successful initiatives and offers recommendations for future directions. By integrating library science principles, this research paper seeks to enhance information access, knowledge dissemination, and interdisciplinary collaboration in the fields of food and nutritional sciences and public health.